The Impact of Transformational Leadership, Career Development, and Work Environment on Organizational Commitment (Survey on CV. Bunda Devina) - Iskandar; Syafrudin, Oding; Suryani, Yeyen; Filallba, Muhammad Algiani Adhia (International Journal Administration, Business & Organization, 2024)
This research analyzes the impact of transformational leadership, career development, and work environment on organizational commitment at CV. Bunda Devina, a company engaged in the andesite natural stone sector, producing a number of raw stones ready for processing and finished natural stones according to demand. This study is a quantitative research using data collection techniques through questionnaires with a survey method. The sampling technique used is saturated sampling with 116 respondents. Data analysis was performed using SPSS. The findings indicate that transformational leadership positively and significantly impacts organizational commitment. Additionally, career development and the work environment both have significantly positive effects on organizational commitment.